Keberadaan Hukum Adat Jawa Dalam Perkawinan Modern - Eko, Febriyanto; Prasetio, Ilham Nur; Sofian, Robby (ALSYS, 2022)
Javanese traditional marriage is a form of syncretism of the influence of Hindu and Islamic customs. In Javanese tradition, offerings, calculations, taboos, and myths are still deeply rooted. Marriage according to the Javanese traditional community is a sincere love relationship between a young man and a woman which basically occurs because of frequent encounters between the two parties, namely a woman and a man. The Javanese proverb says "tresno jalaran soko kulino" which means that love grows because you get used to it. The rapid flow of globalization certainly affects people's lifestyles, including customary law communities. With the modernization process caused by the current of globalization, of course, it will also have an impact on the way of life of indigenous peoples, good culturalization will produce positive manifestations for these indigenous peoples. In the implementation of Javanese traditional marriages there are several stages, the first is the stage of the proposal. This stage is an activity carried out by a man who will propose to a woman, if in the mirror historically the stages of applying have the meaning of proposing because in ancient times between men and women who were about to get married sometimes they still did not know each other so the parents of those who were looking for them mate by asking someone whether or not their daughter has a potential husband.